Crack propagation and toughening mechanism of bilayered short-fiber reinforced resin composite structure —Evaluation up to six months storage in water - Bijelic-Donova Jasmina; Garoushi Sufyan; Lassila Lippo V; Rocca Giovanni Tommaso; Vallittu Pekka K. (Japan, 2022)
Clinically relevant parameters, such as stress intensity factor of bilayered resin composite structure with short fiber base and its stability over time, has yet to be investigated. This study investigated the stress intensity factor of pre-cracked bilayered specimens composed of short fiber resin composite base (SFC) and particulate filler resin composite (PFC) as veneering layer, with a crack located in the PFC layer, 0.5 mm away from the PFC-SFC interface. Monolayered specimens served as controls. All specimens were stored in water at 37°C either for 1 week, 1 month or 6 months before testing. Two-way ANOVA (p=0.05) was used to determine the differences among the groups. Results indicated that SFC base improve the brittleness of the PFC. The type of short fibers affected the crack propagation; fiber bridging in millimeter-scale SFC was the main crack arresting mechanism, whereas fiber pulling observed in micrometer-scale SFC mainly deviated the crack path.